SUCCESS RATE OF UNDESCENDED TESTICLE TREATMENT WITH HUMAN CHORIONIC GONADOTROPIN - Ležakov, Ognjen; Vorgucin, Ivana (Medicinski podmladak, 2019)
Introduction: Cryptorchidism is a disorder of the testicles, when during a physical exam,testicles, one or both of them, are not found in the scrotum, but are found either along theinguinal canal or in the abdomen. Two main modalities of treatment are hormonal and sur-gical treatment.Aim: The aim of this paper was to determine the success rate of hormonal therapy with humanchorionic gonadotropin (hCG) in undescended testicle treatment in patients treated at theInstitute for Child and Youth Health Care in Vojvodina, from January 1, 2010, to December31, 2017.Material and methods: This research included the patients from the Institute for Child andYouth Health Care in Vojvodina ages 0-18, treated from January 1, 2010, to December 31,2017. Medical documentation has been analyzed and interpreted using methods of descrip-tive statistic. The research included boys with undescended testicles, to whom the hormonaltherapy was indicated. Patients were divided into 3 groups (6 years). Thetherapy was applied twice a week, in the course of 5 weeks (hCG 250-1000 IJ/dose). The po-sition 12 months after therapy was used as a final position.Results: The hormonal descend was achieved in 63 patients (62.4%) of the total number ofpatients. Тhe highest success rate was achieved in oldest of our patients (80%).Conclusion: Hormonal therapy with hCG leads to descent in a high percentage, with verylittle transitory adverse effects, and it is an important modality in undescended testiclestreatment.